Il Geoportale del Comune di Jesi - Conti, Tonino (GEOmedia, 2010)
The GeoPortal of Jesi's Municipality The GeoPortal of the Municipality of Jesi born to play a specific role in a more complex project. His main role is to provide correct and updated geographic information to users. The knowledge of the area by the user always provides a return in terms of correctness of the instances that citizens have in the administrative offices. This geo-portal is freely available and all parts are available without restriction including the download area of vector maps. The strength of the system is the continuous updating of published data that is fully automated and it has no effect with normal working conditions, but is based solely on the coding system of unique items.